Pengaruh Pembiayaan Murabahah dan Pembiayaan Musyarakah Terhadap Profitabilitas (ROA) Pada Bank Syariah Indonesia (BSI) Periode 2016-2022 - Erniati; Edi Jatmiko; Marfudin (EKSYDA: Jurnal Studi Ekonomi Syariah, 2024)
This study aims to examine and analyze the Profitability (ROA) of Indonesian Sharia Banks (BSI). The several factors analyzed in influencing Profitability (ROA) are Murabahah Financing and Musyarakah Financing. This study uses a quantitative approach using secondary data, namely data obtained from Bank Syariah Indonesia (BSI) quarterly reports for 2016-2022. Data collection instruments come from Publication Reports of Bank Indonesia and the Financial Services Authority (OJK). The data analysis method used in this study is Multiple Linear Regression Analysis. The results of the partial multiple linear regression test show that murabahah financing has a significant value of 0.041 and musyarakah financing has a significant value of 0.280, so murabaha has a significant effect on profitability and musyarakah has no significant effect on profitability. Simultaneously, all independent variables have a significant influence on profitability, namely a significant value of 0.000 <0.05 .